740 Interesting, oftentimes even trendy! Attitudes of medical students regarding spa medicine (Balneo and PRM Research Journal, 2024)
The popularity of balneology and medical climatology among medical students has scarcely been investigated but may represent a pertinent topic for the field. Methods: A survey was conducted among 53 German medical students (80% female; mean age 22.5 years; 39% pre-clinical stage) on attitudes and interest in spa medicine, their associations with the German terms ‘Kur’ (cure) and ‘Kurortmedizin’ (spa medicine; health resort medicine) and their own health behaviour. Associations with cures were recorded using a visual analogue scale (vas). Results: A majority (72%) of the sample indicated support for the inclusion of more information about spa medicine in university curricula. Spa medicine is associated with older individuals, but with less association to overweight and psychiatric patients. The data for the statements "a spa treatment is up-to-date" and "spa treatment is effective" exhibited a normal distribution in the sample. A significant proportion of respondents reported practicing thermal baths, healthy nutrition, sauna, and Kneipp medicine themselves. Implications: The majority of medical students classified spa medicine as interesting and relevant and do not see it as old-fashioned. This interest should be encouraged in university teaching. Interesting points of reference also arise in relation to predictors of career choice among future physicians.